Elevator model. Design of an elevator model for teaching in the field of automation - Nijdam, Eeke Maria (UiT Norges arktiske universitet, 2019)
For the master of Engineering Design at UiT, the arctic university of Norway, campus Narvik, a master assignment is being executed as a conclusion to the study. In this case the department of industrial automation education had an elevator model design assignment that could be done by an Engineering Design student. This report describes a summary of the design process that has been executed and the results that were obtained. This includes some information about the problem description, market research, function analysis, set of requirements, ergonomics check, morphological overview with resulting concepts, final choice based on quality function deployment, material selection, strength analysis (including tilting check) and feasibility to continue and produce this product locally.